DEVELOPING A DISCOVERY LEARNING-BASED INDONESIAN HISTORY E-BOOK TO INCREASE STUDENTS' SELF-RELIANCE BY USING THE ASSURE MODEL - Hestik Wulandari; Nurul Umamah; Rully Putri Nirmala Puji (JURNAL HISTORICA, 2019)
The objectives of this study are (1) to generate by an Indonesian History e-book based on discovery learning that was validated subject matter experts, linguists, and learning design experts; and (2) to identify the impact of e-books based on discovery learning on increasing the students independence. This study uses the ASSURE development model consisting of (1) analyze learner characteristic; (2) state of performance objective; (3) select methods, media, and materials; (4) utilizing materials; (5) requires leaner participation, and (6) evaluate and revize. The validation results show: (1) the subject matter expert (78% means good criteria); (2) linguists (90% means very good criteria); and (3) design experts (83% means good criteria). The test results of educator users and students get 89% and 86% in which are very good. The trial results show: (1) small group trials have significant differences before (64.31) and after (82.05) e-books utilization with sig. 0.000 and Gain Score 0.5 means a moderate increase; and (2) field trials have significant differences before (53.49) and after (82.61) e-books utilization with sig values 0.000 and Gain Score 0.6 means that there is a moderate increase.